Some notes on a theory of African rhythm advanced by Erich von Hornbostel - Blacking, John (International Library of African Music, 1955)
In an article on African Music written in 1928, Hornbostel offered an explanation of certain features of African rhythms which may puzzle Western ears. Until Hornbostel’s theory has been hammered out and proved true or false—or perhaps true and false, according to its application in different parts of Africa—accurate research into African music is seriously impeded.
Keywords: Ethnomusicology; Musical instruments; Dance; Xylophone music; Syncopation; Africa; Polyrhythm; Drum; Xylophone; Drum music; Criticism; Methods; Interpretation; African Music; Xylophone (Instrument); Drum (Instrument); Musical Meter; Musical Rhythm